Multi-bit organic ferroelectric memory - Khikhlovskyi, Vsevolod; Gorbunov, Andrey V.; Breemen, Albert J. J. M. van; Janssen, René A. J.; Gelinck, Gerwin; Kemerink, Martijn (Organic electronics, 2013)
Storage of multiple bits per element is a promising alternative to miniaturization for increasing the information data density in memories. Here we introduce a multi-bit organic ferroelectric-based non-volatile memory with binary readout from a simple capacitor structure. The functioning of our multi-bit concept is quite generally applicable and depends on the following properties for the data storage medium: (a) The data storage medium effectively consists of microscopic switching elements (‘hysterons’). (b) The positive and negative coercive fields of each hysteron are equal in magnitude. (c) The distribution of hysteron coercive fields has substantial width. We show that the organic ferroelectric copolymer P(VDF-TrFE) meets these requirements. All basic properties of our device were measured and modeled in the framework of the dipole switching theory (DST). As a first example we show the possibility to independently program and subsequently read out the lower, middle and upper parts of the hysteron distribution function, yielding a 3-bit memory in a single capacitor structure. All measured devices show good state reproducibility, high endurance and potentially great scalability.